Mouse Models of Arteriosclerosis : From Arterial Injuries to Vascular Grafts - Xu, Qingbo (American Society for Investigative Pathology, 2004)
Animal models are designed to be preliminary tools for better understanding of the pathogenesis, improvement in diagnosis, prevention, and therapy of arteriosclerosis in humans. Attracted by the well-defined genetic systems, a number of investigators have begun to use the mouse as an experimental system for arteriosclerosis research. Hundreds of inbred lines have been established, and the genetic map is relatively well defined, and both congenic strains and recombinant strains are available to facilitate genetic experimentation. Because arteriosclerosis is a complicated disease, which includes spontaneous (native) atherosclerosis, transplant arteriosclerosis, vein graft atherosclerosis, and angioplasty-induced restenosis, several mouse models for studying all types of arteriosclerosis have recently been established. Using these mouse models, much knowledge concerning the pathogenesis of the disease and therapeutic intervention has been gained, eg, origins of endothelial and smooth muscle cells in lesions of transplant and vein graft atherosclerosis. This review will not attempt to cover all aspects of mouse models, rather focus on models of arterial injuries, vein grafts, and transplant arteriosclerosis, by which the major progress in understanding the mechanisms of the disease has been made. This article will also point out (dis)advantages of a variety of models, and how the models can be appropriately chosen for different purposes of study.